Improving central venous catheter care with chlorhexidine gluconate dressings: evidence from a systematic review and Meta-analysis - Huilin Xu; Min Zhu; Shenghong Xu; Lanzheng Bian (BMC, 2024)
Abstract Background The prevention of catheter-related bloodstream infections (CRBSI) is a critical priority in the clinical management of central venous catheters (CVCs). This meta-analysis aims to evaluate the efficacy of chlorhexidine gluconate antibacterial dressings in the context of CVC care. Methods A systematic literature search was performed in PubMed, Web of Science, Embase et al. databases up to May 28, 2024. The search targeted randomized controlled trials (RCTs) that investigated the impact of chlorhexidine gluconate antibacterial dressings on CVC-related outcomes. The meta-analysis was conducted using RevMan 5.3 software. Results The final analysis included 14 RCTs involving a total of 8920 patients with CVCs, with participants divided into a chlorhexidine antibacterial dressing group (n = 4731) and a control group (n = 4189). The chlorhexidine dressing group demonstrated a statistically significant reduction in the incidence of CRBSI compared to the control group, with a relative risk (RR) of 0.48, 95% confidence interval (CI) 0.36-0.64, P < 0.001. The chlorhexidine dressing group also showed a significant decrease in bacterial colonization, with an RR of 0.46, 95% CI 0.38-0.55, P < 0.001. Assessment of publication bias through funnel plot asymmetry and Egger's test revealed no significant bias in the included studies (all P > 0.05). Conclusions There is a notable reduction in the incidence of CRBSI and bacterial colonization in patients with CVCs through the application of chlorhexidine gluconate dressings. Given the compelling evidence, the integration of these dressings into standard nursing care protocols for the management of CVCs is advocated.